Hardships in Italian Prisons During the COVID-19 Emergency: The Experience of Healthcare Personnel - Testoni, Ines; Francioli, Giada; Biancalani, Gianmarco; Libianchi, Sandro; Orkibi, Hod (Frontiers in Psychology, 2021)
Background: The recent COVID-19 pandemic has highlighted the deficiencies that characterize the functioning of the Italian national health system. Prisons have always mirrored the most radical expressions of these weaknesses. During the early stages of the pandemic, prison facilities across Italy underwent a series of changes dictated by the need to ensure the safety of the prisoners and staff. The adoption of these rules contributed to a total or partial redefinition of many central facets of life in prison, such as intake procedures for new arrivals and the ways prisoners were allowed to communicate with their families. Objectives: The aim of this qualitative study was to analyze the testimony of penitentiary healthcare workers in prisons throughout Italy to determine the impact of COVID-19 on their professional and personal lives. Participants: 38 participants were contacted and 20 decided to participate in the interview. The sample was made up of 10 women and 10 men. All the participants were members of the healthcare staff of a penitentiary facility (psychologists, psychiatrists, physicians, and nurses). All were recruited through an Italian association whose mission is the development, promotion, and implementation of social solidarity projects including prisoners' social and health care. This study was facilitated through representatives serving in nine different regions of Italy. The participants were divided according to their professional roles in prisons. Method: In-depth interviews were conducted by telephone or online using telecommunication platforms (e.g., Zoom, WhatsApp, Skype). The transcribed texts underwent thematic analysis using the Atlas.ti software to identify patterns of meaning across the dataset.